Hypertension in periand postmenopausal women: mechanisms, management, observation - E. A. Polyakova; A. O. Konradi; E. I. Baranova; A. S. Galyavich; Y. V. Zhernakova; T. N. Novikova; N. I. Tapilskaya; O. N. Tkacheva; O. D. Ostroumova; V. V. Skibitsky; G. A. Chumakova (Российский кардиологический журнал, 2024)
An important role in the development and evolution of hypertension in females is applied to sex hormones. Estrogen deficiency and hyperandrogenism, characteristic of periand postmenopause, are links in the pathogenesis of hypertension in this period of a woman's life and are accompanied by an increase in sympathetic nervous system activity, renin-angiotensin-aldosterone system activation, salt sensitivity, abdominal obesity and metabolic syndrome, left ventricle hypertrophy, left atrial dilatation with a high risk of atrial fibrillation, stroke and heart failure development. The paper discusses antihypertensive therapy during periand postmenopause, effectiveness and tolerability of different drug classes. Special attention is paid to the mechanism of action of selective I1-imidazoline receptor agonist moxonidine, which in women during this period both effectively reduces high blood pressure and has a beneficial metabolic effect, what is documents in studies of monotherapy, combined antihypertensive therapy with major classes and in combination with menopausal hormone therapy. The paper presents the joint expert opinion concerning above mentioned issues.